Continuous structure modification of metal-organic framework glasses via halide salts - Fengming Cao; Søren S. Sørensen; Anders K. R. Christensen; Samraj Mollick; Xuan Ge; Daming Sun; Anders B. Nielsen; Niels Chr. Nielsen; Nina Lock; Ronghui Lu; Rebekka Klemmt; Peter K. Kristensen; et al. (Nature Communications)
Abstract Melting and glass formation of metal-organic frameworks (MOFs) allow them to be processed into bulk materials. However, two major challenges remain: only a small fraction of MOF crystals undergo melting and glass-formation, and no well-established strategies exist for tuning MOF glass structures and properties. Here, we address both challenges through co-melting of zeolitic imidazole frameworks (ZIFs), a subset of MOFs, with heterocycle-based halide salts. The salt acts as a chemical “modifier”, akin to the role of alkali modifiers in traditional silicate glasses, e.g., allowing the melting of ZIF-8 that otherwise decomposes prior to melting. Through experimental and computational analyses, we show that the salts depolymerize the ZIFs, enabling continuous tuning of the fraction of bridging to non-bridging imidazolate linkers and, thereby, the thermal and mechanical properties. The proposed strategy enables diversification of MOF glass chemistry, tunable structures and properties, and ultimately an increased number of glass-forming MOFs with improved functionalities.